2020
DOI: 10.1002/ps.6190
|View full text |Cite
|
Sign up to set email alerts
|

Non‐host volatiles disturb the feeding behavior and reduce the fecundity of the green peach aphid, Myzus persicae

Abstract: BACKGROUND The association of crops of value with companion plants could be one of the strategies to reduce the harmful effects of pests. We hypothesize that volatile organic compounds (VOCs) emitted by some aromatic plants may negatively impact M. persicae, disturbing its feeding behavior and consequently its reproduction. RESULTS VOCs emitted from six potential companion plant species affected the reproduction of M. persicae feeding on pepper plants, Capsicum annuum. Reproduction of M. persicae was reduced w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Although for D. plantaginea aphids the total time allocated to stylet penetration (i.e., general probing phase) was unchanged, garlic EO volatiles disrupted the feeding activity through a greater number of probes performed (n_Pr). Dardouri et al (2021) showed that the repellent effect of the two companion plants Tagetes patula L. (marigold) and Ocimum basilicum L. (basil) translated into greater numbers of probes (n_Pr) and a shorter total duration of probing (s_Pr) for M. persicae on sweet pepper. Although the pathway phase was not altered in our experiment, garlic EO seemed to have impacted behavioral phases within mesophyll occurring before the initiation of sap ingestion, which was shown by an increase in the median duration of stylet derailment events.…”
Section: Discussionmentioning
confidence: 99%
“…Although for D. plantaginea aphids the total time allocated to stylet penetration (i.e., general probing phase) was unchanged, garlic EO volatiles disrupted the feeding activity through a greater number of probes performed (n_Pr). Dardouri et al (2021) showed that the repellent effect of the two companion plants Tagetes patula L. (marigold) and Ocimum basilicum L. (basil) translated into greater numbers of probes (n_Pr) and a shorter total duration of probing (s_Pr) for M. persicae on sweet pepper. Although the pathway phase was not altered in our experiment, garlic EO seemed to have impacted behavioral phases within mesophyll occurring before the initiation of sap ingestion, which was shown by an increase in the median duration of stylet derailment events.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this structure modifies the innate behavior of B. tabaci for settling and feeding on the abaxial surface of tomato leaves [46]. The VOCs from Ocimum basilicum L. and Tagetes patula L. also reduced sustained feeding and increased nonproductive probing and searching [47]. The surface resistance characteristics of Rough Lemon, Olinda, and Eureka mentioned above remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Psyllid-infested pear trees produced more limonene, α-farnesene, and δ-cadinene after infestation, as well as green leaf volatiles such as (Z)-3-hexen-1-yl acetate and (Z)-3-hexen-1-ol [44]. Peach trees that were infested with the green peach aphid released higher levels of β-ocimene, α-and β-farnesene, and E-nerolidol [43]. Many VOCs also stimulate the volatile defenses of nearby plants (defensive priming) or act as kairomones for attracting the natural predators or parasitoids of the target pest, demonstrating complex inter-trophic relationships between plants and their pests [41].…”
Section: Introductionmentioning
confidence: 99%
“…Among the many roles of leaf volatiles are those of attracting pollinators, repelling herbivores, or attracting their natural predators. Induction of terpenoids as a plant defense following insect herbivory has been widely reported in both annual and perennial crop plants including corn [41], citrus [42], peach [43], and pear [44]. Psyllid-infested pear trees produced more limonene, α-farnesene, and δ-cadinene after infestation, as well as green leaf volatiles such as (Z)-3-hexen-1-yl acetate and (Z)-3-hexen-1-ol [44].…”
Section: Introductionmentioning
confidence: 99%